The Effect of Work Environment, Compensation, Empowerment Leadership on Employee Loyalty at Maju Jaya Abadi Company Yogyakarta - Aufa Ilman, Ahdan; Didik Subiyanto; Mohammad Ahyar Syafwan Lysander (Jurnal Manajemen, 2025)
Employee loyalty is a very important thing for the company because it is needed, especially for the courage of employees who show devotion to the organisation regardless of the company’s circumstances. This study aims to examine the effect of employee loyalty at Maju Jaya Abadi Yogyakarta Company through work environment, compensation, and empowerment leadership. The study population was 300 employees, the sample was calculated using the Slovin formula to be 75 samples, with the sampling technique using accidental sampling. The analytical technique used in answering the hypothesis is multiple linear regression, the processing is assisted by SPSS software version 26. Based on testing the research results show that partially the work environment and compensation have no effect on employee loyalty and empowerment leadership affects employee loyalty while the work environment, compensation, and empowerment leadership simultaneously have a significant effect on employee loyalty